2001
DOI: 10.1002/1097-0142(20010415)91:8<1494::aid-cncr1157>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncoprotein 18 overexpression increases the sensitivity to vindesine in the human lung carcinoma cells

Abstract: BACKGROUND Oncoprotein 18 (op18) was first isolated as a molecule overexpressed in several malignant cells, suggesting a function of op18 in malignant processes, such as differentiation in hematologic malignancies, op18 also was found to enhance microtubule deassembly in the cells. Antimitotic agents that bind to tubulin have been used for chemotherapy to treat solid tumors, such as lung carcinoma. Vinca alkaloids, such as vindesine and vincristine, have commonly been used for chemotherapy of nonsmall cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 17 publications
3
26
2
2
Order By: Relevance
“…66 Antimitotic agents that bind to tubulin have been used for chemotherapy to treat various malignancies. Op18 cDNA was transfected to SBC-3 human lung carcinoma cells, and stable transfectants were isolated.…”
Section: Op18 As a Therapeutic Targetcontrasting
confidence: 75%
“…66 Antimitotic agents that bind to tubulin have been used for chemotherapy to treat various malignancies. Op18 cDNA was transfected to SBC-3 human lung carcinoma cells, and stable transfectants were isolated.…”
Section: Op18 As a Therapeutic Targetcontrasting
confidence: 75%
“…The presence of multiple transcription factor recognition sequences gives us more confidence of the possibility of a site for PDEF binding on STMN. STMN is overexpressed in many human malignancies including leukemia (42), lymphoma (43), neuroblastoma (44); ovarian (45), prostatic (46), breast (47,48) and lung cancer (49). In many of these cancers, high STMN expression correlates with bad prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stathmin provides an attractive molecular target for disrupting the mitotic apparatus and arresting the growth of malignant cells. In addition, several studies have shown that stathmin is a potential therapeutic target because a stathmin-transfected lung cancer cell line has increased sensitivity to Vinca alkaloids (Nishio et al, 2001), and antisense inhibition of stathmin expression showed a synergistic apoptotic effect in combination with paclitaxel treatment (Iancu et al, 2000). Further studies with a larger population will improve our ability to treat this cancer.…”
Section: Discussionmentioning
confidence: 99%